Social and Labor Adaptation of People with Disabilities by Means of Production of Items of Folk Art: Evidence from Sociological Study - Khaliman, Zhanna Nikolaevna; Alexeeva, Galina V.; Zrutina, Irina V.; Goltsova, Xenia V.; Thi, Tran Duy (International Journal of Economics and Financial Issues, 2015)
The article looks at the issues of integration of people with disabilities into a contemporary Russian society by means of utilization of their labor potential in the production of items of folk art with consideration of experience of this kind of activities in Vietnam. The relevance of this theme arises due to the lack of a much needed attention on the part of the government in formation of socially adequate and non-discriminatory conditions for life and activities of people with disabilities, which would allow them to overcome an image of a passive and dependent disability in the mass consciousness and disabled peoples’ own self-consciousness. The most important condition of a successful integration of people with disabilities is their professional self-determination and employment. The study shows that people with disabilities face significant difficulties in identification of their place in life from the perspective of their professional employment. A priority area of employment of people with disabilities is their involvement in decorative arts, which encourages their full integration in a society, as most often they cannot adapt to the usual conditions of life and cannot compete on the labor market as equals with people without disabilities. Considering the fact that labor rehabilitation of people with disabilities by means of their involvement with decorative arts is not sufficiently spread in Russia there is a need to actively spread the media message about the advances of the people with disabilities in Vietnam in the sphere of production of items in decorative arts. Keywords: People with disabilities, social integration, labor rehabilitation, social policy, labor market, professional niches, folk art JEL Classifications: I14; J71; J23